Simulation Modelling In a Availability Thermal Power Plant - Sorabh Gupta; P.C. Tewari (Journal of Engineering Science and Technology Review, 2014)
The present paper deals with the opportunities for the availability simulation modelling and maintenance decision making in thermal power plant. These opportunities will be identified by evaluation of a simulation model to be built for the steam and water analysis system (SWAS) of a thermal power plant. This feasibility study covers two areas: development of an availability simulation model and decision making with the help of developed model. The present system of thermal plant under study consists of six subsystems with two possible states: working and failed. A probabilistic simulated model using Markov approach has been developed considering some assumptions. Availability decision matrix for each subsystem is also developed, which provide various availability levels. On the basis of this study, performance or availability of each subsystem of SWAS is analyzed and then maintenance priorities are decided for present system.